2021
DOI: 10.1097/nnd.0000000000000787
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Simulation Use in Transition to Practice Nurse Residency Programs

Abstract: Representatives of three international associations reviewed literature published from 2009 to 2018 to ascertain the effectiveness of simulation use in transition to practice programs for newly licensed registered nurses (NLRNs). A review of nine quantitative studies demonstrated that simulation positively influences NLRN self-perception of skills, competence, readiness for practice, and confidence. However, evidence of objective measures of NLRN competence and the impact of simulation on patient and organizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…23,29,35 Extended programs that last between 12 and 18 months and include a comprehensive review of concepts and simulated experiences are recommended. 36,37 Given the ongoing demands of direct care nurses, self-care and resilience training should be included. 37 Opportunities to engage with residency cohort members during the first year can also enhance resilience as they share experiences, problem-solve, and form relationships with peers and nurse leaders.…”
Section: Recommendations To Promote Retention and Reduce Ngn Turnovermentioning
confidence: 99%
See 1 more Smart Citation
“…23,29,35 Extended programs that last between 12 and 18 months and include a comprehensive review of concepts and simulated experiences are recommended. 36,37 Given the ongoing demands of direct care nurses, self-care and resilience training should be included. 37 Opportunities to engage with residency cohort members during the first year can also enhance resilience as they share experiences, problem-solve, and form relationships with peers and nurse leaders.…”
Section: Recommendations To Promote Retention and Reduce Ngn Turnovermentioning
confidence: 99%
“…A structured, evidence-based program can facilitate transition to practice and promote a safe environment 23,29,35. Extended programs that last between 12 and 18 months and include a comprehensive review of concepts and simulated experiences are recommended 36,37. Given the ongoing demands of direct care nurses, self-care and resilience training should be included 37.…”
Section: Recommendations To Promote Retention and Reduce Ngn Turnovermentioning
confidence: 99%
“…The choice of a validated and psychometric-tested instrument for the measurement of the ability to care in acute situations should, however, be considered a methodological strength. 12 Furthermore, the data in this study were self-reported. However, the use of self-reported data is frequently used in simulationbased studies, 34 owing to a lack of objective measures.…”
Section: Limitationsmentioning
confidence: 99%
“…11 A review from the specific context of transition program studies indicated that the use of simulation-based education improved NGNs' perceptions of their skills, confidence, competence, and readiness for practice. 12 Elsewhere, simulations have been reported to enhance NGNs' ongoing development of clinical judgment and their ability to notice patient issues and reflect on care experiences. 13 Despite literature indicating that simulation-based education is beneficial, there is no consensus regarding the types and timing of simulations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation